INTERTEXTUAL COMPARISON OF TURKISH DIALECTS VIA ENTROPY APPROXIMATION. - SARAÇLI, Sinan; AKIN, Cüneyt (Electronic Turkish Studies)
Entropy, a very old term, was developed by Clausius in thermodynamics toward the middle of the 19 century. In thermodynamics or statistical mechanics, entropy is the measure of the level of the existing disorder in a thermo-dynamical system. Today, entropy optimization methods has important applications in the fields such as statistics, mathematics, geography, space sciences, economics, finance, marketing, system analysis, image processing, and model selecting. Furthermore, literature has many works which compare superiority of different languages. There is no such work in the Turkish language. We believe that such future works in the field will fill this gap. Using entropy methods, the present work compares the Göktürk language (the original text), Turkish (translation), Kyrgyz (translation) and Kazakh (translation) in terms of their language characteristics. The MATLAB software was used. An example application was conducted in order to enable the work to be more understandable for the experts working in the field of the Turkish language. Entropy between the texts in the Orkhon inscriptions and their Kyrgyz and Kazakh translations was done. The work used the mutual translations of the same text in the Göktürk language, Turkish, Kazakh and Kyrgyz. Entropy of each text was calculated by the MATLAB software and shown in the tables. The results were obtained by analyzing the text which was used in the application by the program which calculates entropy of any text which was previously entered in the system. The appendix 1 includes the MATLAB codes to calculate eny given text. Any researchers can calculate the entropy of their text through the software by entering their